The Effect of Profitability, Debt Policy, Political Connections, Economic Crisis on Tax Aggressiveness - Ridwansyah, Ridwansyah; Indayani (PT Inovasi Pratama Internasional, 2024)
The primary goal of this study is to analyze the impact of economic and political power, debt policy, and political influence on tax aggressiveness during times of economic uncertainty. In this study, we choose as examples health and pharmaceutical firms trading on the Indonesia Stock Exchange between the years 2018 and 2021. To test for the predicted difference between before and after the covid 19 epidemic, researchers utilized multiple regression and other tests (paired sample t-test) in SPSS version 23. This research backs up the notion that fiscal stability and profitability affect tax aggressiveness. There was no difference in the prevalence of tax evasion strategies either before or after the Covid 19 pandemic, and neither debt policies nor political relationships seemed to have any influence on tax aggression. Using research findings to inform decision making or policy implementation may boost a company's future success. In addition to building on earlier replication attempts, this work also puts to the test comparisons made before and during the COVID-19 epidemic, making it a significant piece of research.